Pharmacist insights into adolescent human papillomavirus vaccination provision in the United States - Jessica Y. Islam; Joann F. Gruber; Deanna Kepka; Manju Kunwar; Sara B. Smith; Mitchel C. Rothholz; Noel T. Brewer; Jennifer S. Smith (Taylor & Francis Group, 2019)
HPV vaccination coverage in the United States (US) falls short of the Healthy People 2020 goal of 80% coverage among 13-15 year-old adolescents. Pharmacies are a promising alternative vaccine delivery site that may increase access to HPV vaccination. Our objective was to assess pharmacists' insights into HPV vaccination provision to adolescents. We recruited 40 licensed pharmacists in eight states with different pharmacy vaccination laws: Alabama, California, Indiana, Kentucky, Maine, Tennessee, Texas, and Washington. Eligible pharmacists either previously provided or were currently providing HPV, tetanus-diphtheria-pertussis, or meningococcal vaccines to adolescents aged 9-17 years. Pharmacists were administered a semi-structured survey to explore insights into HPV vaccination provision. Forty-five percent of surveyed pharmacies offered HPV vaccination to adolescents. Pharmacists' reported challenges to providing HPV vaccination were parental consent (28%), tracking and patient recall (17%), perceived stigma of vaccination (17%), and education about or promotion of vaccination (17%). Pharmacists offering HPV vaccination sent patient reminders for vaccines with multiple doses (89%) and utilized telephone reminders (72%). Pharmacists informed patients' primary care providers of HPV vaccination doses most commonly through fax (72%) and updating electronic medical records (22%). One-third of pharmacists reported vaccination provision using the state immunization information system (IIS). Seventy-five percent reported vaccination rates could be increased at their respective pharmacy. Pharmacies are underutilized, although highly accessible, for HPV vaccination in the US. National efforts should expand educational programs to improve public awareness of in-pharmacy HPV vaccination, and improve the utilization of state IIS for reporting immunization coverage of adolescents by pharmacists.